2020
DOI: 10.18203/2394-6040.ijcmph20205692
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-epidemiological profile of high altitude pulmonary edema

Abstract: Background: With increase in the footfall to mountainous areas for occupational and recreational purposes, tackling the burden of high-altitude illnesses is a growing public health challenge. High-altitude pulmonary edema (HAPE) is a serious medical condition with peculiar epidemiological characteristics. HAPE is a significant cause of morbidity and mortality among Indian soldiers posted to high-altitude areas. Aims and objectives of the study were to study the common clinical presentation of HAPE among Indian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
(18 reference statements)
0
4
0
Order By: Relevance
“… 15 The mean age at the onset of HAPE in this study was 34 years, which is similar to the mean age observed in the study by Hultgren. 15 A previous epidemiological study from India 16 also showed that the likelihood of HAPE decreased with age and showed a relatively low incidence in the age range of 36–45. They found comparatively high diagnoses in the age range lower than 35, which is consistent with the findings of our study.…”
Section: Discussionmentioning
confidence: 94%
“… 15 The mean age at the onset of HAPE in this study was 34 years, which is similar to the mean age observed in the study by Hultgren. 15 A previous epidemiological study from India 16 also showed that the likelihood of HAPE decreased with age and showed a relatively low incidence in the age range of 36–45. They found comparatively high diagnoses in the age range lower than 35, which is consistent with the findings of our study.…”
Section: Discussionmentioning
confidence: 94%
“…1,2 It takes 2-5 days and an altitude above 3000 m for its complete manifestation. [3][4][5][6] While rapid ascent is an important risk factor, overexertion and ascending with respiratory tract infection further increases the risk. 7,8 The diagnosis becomes challenging when both HAPE and pneumonia coexist or if a recent respiratory tract infection has occurred.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 It takes 2–5 days and an altitude above 3000 m for its complete manifestation. 3 , 4 , 5 , 6 While rapid ascent is an important risk factor, overexertion and ascending with respiratory tract infection further increases the risk. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation